Determination of the proximate and functional properties of brown glutinous NSIC RC 13 rice (Oryza sativa) flour - Uy, Jared Eiser A. (College of Home Economics, University of the Philippines Diliman, 2013)
Functional properties of NSIC Rc 13 brown glutinous rice flour were determined in order to establish whether they are significantly different from commercially available polished glutinous rice flour. Proximate analysis on the flours and sensory tests on palitaw, a local sweet and sticky rice cake, were also conducted. Brown glutinous rice flour was found to have significantly higher (p<0.05) values for water absorption index, water solubility index, least gelation concentration, pasting temperature, fat content, ash content, and crude fiber content; while the oil absorption capacity, pasting properties (peak, trough, breakdown, final, and setback viscosities), and moisture content had significantly higher values for polished rice flour. Sensorially, the palitaw made from brown glutinous rice flour was significantly (p<0.05) less acceptable and less preferred in terms of appearance, flavor, and overall acceptability. These results suggest that the brown rice flour does not have better functionality than polished rice flour, with water absorption index and water solubility index being the only functional properties that are more favorable for the former. However, brown glutinous rice flour may be considered for its nutritional contribution, given its high ash and crude fiber contents. Further research on the functional properties of brown glutinous rice flour or the replication of this study is recommended in order to fulfill the objective of the study to more thoroughly. Moreover, for future attempts, the application of brown glutinous rice flour in other food products besides palitaw for sensory testing is suggested due to the relatively poor acceptance and preference of palitaw made from brown glutinous rice flour compared to that made from polished glutinous rice flour.